БОБУРНИНГ ДАВР ВА КЕЧМИШ ТАРИХИГА ДОИР ҚАРАШЛАРИ - Сулаймонов, И.И. (SCIENCE and SOCIETY, 2018)
The article is devoted to the analysis of the views of Babur of his time and the last era as well as the ideas of winners and losers. The researcher tries to study the problem of the concept of personality in the work ―Baburname‖.
Keywords: Bobur; historical person; psychological situation; conflict and experience; the truth of history and literary-artistic interpretation; political and literary environment; winner and loser